The Validity of Purchasing Land Underhand in Land Sale and Purchase Disputes in Kutai Kartanegara District (A Study of Tenggarong District Court Decision Number 91/Pdt.G/2019) - Pradoto, Waluyo Slamet; Broto Laksito, FX. Hastowo (Journal of Law and Economics, 2024)
The purpose of this research is to analyze the legal considerations and consequences arising from the issuance of Tenggarong District Court Decision Number 91/Pdt.G/2019, which resolved a dispute over the sale and purchase of freehold land involving the Plaintiff (Warda), Defendant I (Octavianus P), Defendant II (Ahmad Rakbini), and the Co-Defendant (National Land Agency Office, Kutai Kartanegara Regency). The research was initiated due to the Plaintiff's lawsuit filed at the Tenggarong District Court, stemming from challenges in transferring or changing the ownership name of a plot of land purchased privately from Defendant II. These difficulties arose because the Defendants' current addresses were unknown, preventing the completion of administrative requirements for registration with the National Land Agency. Consequently, the Plaintiff sought a court ruling to validate the payment receipt as evidence of the land purchase. This study employs a normative juridical method with a descriptive approach, utilizing secondary data sources and qualitative analysis. The findings indicate that the court partially granted the Plaintiff's claims, legally authorizing the transfer of land ownership from the Defendant to the Plaintiff, based on a private sale agreement and supported by a payment receipt. The court issued the decision in verstek since the Defendants, including the Co-Defendant, did not attend the proceedings, provide information, or appoint legal representation.